Clinical neuroprosthetics: Today and tomorrow. (October 2019) - Lee, Morgan B.; Kramer, Daniel R.; Peng, Terrance; Barbaro, Michael F.; Liu, Charles Y.; Kellis, Spencer; Lee, Brian
Highlights: Clinical BCI are standard practice for historically difficult to treat conditions. Development of closed-loop systems requires the discovery of reliable biomarkers. Future BCI will include closed-loop devices for expanded neurological indications. Future motor BCI will incorporate sensory feedback, creating a closed-loop system. The development of motor BCI is linked to the success of clinical BCI. Abstract: Implantable neurostimulation devices provide a direct therapeutic link to the nervous system and can be considered brain-computer interfaces (BCI). Under this definition, BCI are not simply science fiction, they are part of existing neurosurgical practice. Clinical BCI are standard of care for historically difficult to treat neurological disorders. These systems target the central and peripheral nervous system and include Vagus Nerve Stimulation, Responsive Neurostimulation, and Deep Brain Stimulation. Recent advances in clinical BCI have focused on creating "closed-loop" systems. These systems rely on biomarker feedback and promise individualized therapy with optimal stimulation delivery and minimal side effects. Success of clinical BCI has paralleled research efforts to create BCI that restore upper extremity motor and sensory function to patients. Efforts to develop closed loop motor/sensory BCI is linked to the successes of today's clinical BCI.